Manajemen Sarana Prasarana Dalam Meningkatkan Efektivitas Operasional Sekolah Dan Media Pembelajaran Siswa di SMAN 1 Rogojampi Banyuwangi - Baraz Yoechva Alfaiz; Dadang Ahmad Sujatnika; Adang Sutarman (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This study aims to investigate the planning, implementation and evaluation of the management of educational facilities and infrastructure at State Senior High School 1 Rogojampi Banyuwangi with a focus on its effectiveness in improving the quality of educational services. The research method used is a case study with a qualitative approach. Data was collected through observation, interviews and document analysis. The research results show that the planning of educational facilities and infrastructure was carried out comprehensively, involving all school members and following standard operating procedures. Implementation is carried out by paying attention to short-, medium-, and long-term planning, as well as through procurement, inventory, distribution and maintenance of facilities. Evaluations are carried out regularly, including monthly meetings, semester meetings, and school self-evaluation, to evaluate progress, achievements, and strategies that have been implemented. The implication of these findings is the need to continue to increase participation, maintenance, and internal and external evaluation to optimize the management of educational facilities and infrastructure.